Writer’s Cramps in Forensic Document Examination - Alkan, Nevzat; Uzun, Nurten; Tüzün, Birgül; Kızıltan, Meral Erdemir; Sözen, Mehmet Şevki (The Bulletin of Legal Medicine, 2000)
There are a lot of factors that influence handwriting and signatures. Among these factors can be listed some of them such as the position of the body, writing surface, writing instrument, emotional state, various drugs, alcohol, neuroleptic or stimulant drugs, physical and mental diseases and aging. Writer's cramp is a focal dystonia that holds upper extremities as a most frequent dystonia type. This disease effects handwriting rapidly and seriously. In our study we evaluated the handwriting samples of 38 patients with writer's cramp. Handwriting and signatures of the patients that have been diagnosed as writer' s cramp or writer's cramp and writer's tremor were examined according to the criteria used in forensic document examination. 5 of 38 patients were female. The patients' ages were between 24-80 and medium age was 46.5. Medium disease period was 3.3 years. 20 of 38 patients started to write with a normal handwriting and deteriorated after writing a few sentences later and handwriting of 18 of 38 patients were broken in onset and got more deteriorated with writing. Handwriting of 6 of 38 patients displayed a pueril character. Handwriting and signature examination is an important working area in daily forensic medicine practices. Thus all document examiners must be careful and well-informed about various diseases and their effects upon handwriting and signatures. Otherwise, misinterpretation in the expertise reports will be inevitable in forensic document examination.Key Words: Writer’s cramp, forensic document examination, forensic medicine, handwriting
Keywords: writer’s cramp; forensic document examination; forensic medicine; handwriting